Impact of nutritional status on the quality of life of advanced cancer patients in hospice home care. - Shahmoradi, Negar; Kandiah, Mirnalini; Loh, Su Peng (Asian Pacific Organization for Cancer Prevention, 2009)
Background: Cancer patients frequently experience malnutrition and this is an important factor in impaired quality of life.